WIDER perspectives on global development - Atkinson, Anthony B. 1944-2017; Basu, Kaushik 1952-; Bhagwati, Jagdish N. 1934-; North, Douglass Cecil 1920-2015 (Palgrave Macmillan UK, 2005)
This volume brings together some of the most influential scholars in development economics to explore how to improve the well-being of the poor, how to design effective structures and institutions for poverty reduction and what the role of economic, political and social dimensions are (and should be) in global development. Issues addressed include globalization; both its governance and a historical perspective; inequality, of income, and the potential for conflict; trade and labour practises in a transitional and developing world, and; the natures and characteristics of institutions and markets
Keywords: Political economy; International relations; International economics; Economic policy; Development economics; Wirtschaftsentwicklung; Wirtschaftspolitik; Entwicklungspolitik; Entwicklungsökonomie; Globalisierung; Entwicklungsländer; Aufsatzsammlung; Bibliografie